Analisis Pengetahuan Dan Sikap Petani Dalam Bertani Jagung Di Bawah Tegakan Terhadap Kelestarian Hutan Kecamatan Geyer Kabupaten Grobogan - Atik Ulfa Rofiah; Eva Banowati (Edu Geography, 2023)
The purpose of this research are to analyze the knowledge and the attitude of forest farmers in farming corn under canopy cover Geyer district Grobogan regency. The population studied is farmers pesanggem in Jambangan village. Sample collection using purposive sampling with 97 respondents. Data collection was carried out by observation, documentation, questionnaires and interviews. The data analysis techniques using descriptive percentages and multiple linier regression. The result showed that farmers knowledge had an average of 74,40% with good criteria, while farmers attitude had an average of 64,51% with good criteria. After conducting multiple linear regression test simultaneously, there is an influence of knowledge and attitude of farmers in corn farming under forest canopy by 3%, meaning that the contribution of knowledge and attitude of farmers in this study does not have plenty effect on farming under forest because the rest is influence by other variables outside the arranged model. Farmers need to raise the participation in activities or counseling which held by Perhutani to increase knowledge so that it could give good impact for them.